The Relationship Between Self-Efficacy, Self-Development, and Human Resource Competence with Innovative Organizations in Higher Education - Suherman, Agus; Suherman, Suherman; Anriani, Nurul (FKIP Universitas Lampung, 2025)
The Relationship Between Self-Efficacy, Self-Development, And Human Resource Competence With Innovative Organizations In Higher Education. Objectives: This study aims to analyze the relationship between self-development, self-efficacy, and human resource (HR) competence in fostering innovation within organizations. Methods: To address this issue, this research employs a quantitative approach using a survey method. Data collection was conducted through a questionnaire. The analysis model applied is path analysis using SPSS (Statistical Package for the Social Sciences), with respondents comprising program heads, lecturers, and educational staff at higher education institutions, totaling 350 individuals. Findings: The results indicate that there is no significant collective influence of all variables on organizational innovation. However, each variable plays a distinct role in shaping innovation. Self-efficacy directly influences organizational innovation, while self-development contributes to innovation only when strongly linked with HR competence. This suggests that fostering a highly innovative organization requires strengthening self-efficacy alongside improving self-development and HR competence. Conclusion: To enhance organizational productivity and innovation, it is crucial to first improve self-efficacy and self-development among lecturers and educational staff. Strengthening these aspects will enhance lecturer competence, which directly impacts the organization's capacity to innovate. Organizations should prioritize initiatives that support professional growth and self-efficacy to create a more sustainable and innovative environment. Keywords: self-efficacy, self-development, human resource competence, innovative organizations.